2001
DOI: 10.2337/diabetes.50.10.2396
|View full text |Cite
|
Sign up to set email alerts
|

A Major Gene Effect on Fasting Insulin and Insulin Sensitivity in Familial Combined Hyperlipidemia

Abstract: The most common inherited dyslipidemia, familial combined hyperlipidemia (FCHL), is associated with insulin resistance. Whether insulin sensitivity in these families is inherited is not known. Therefore, we investigated the inheritance of insulin sensitivity in 352 nondiabetic family members from 37 families with FCHL, 105 of whom had undergone testing using the hyperinsulinemiceuglycemic clamp technique for the measurement of insulin sensitivity. First, complex segregation analysis of fasting insulin levels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Type 2 diabetes was a specific exclusion criterion in the present study. However, because previous studies have indicated that patients with FCHL may have impaired glucose tolerance and insulin resistance, 8,19,21,24,40,41 some of the linkage signals we obtained close to this marker in our analyses might relate to a common metabolic abnormality in FCHL and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 53%
“…Type 2 diabetes was a specific exclusion criterion in the present study. However, because previous studies have indicated that patients with FCHL may have impaired glucose tolerance and insulin resistance, 8,19,21,24,40,41 some of the linkage signals we obtained close to this marker in our analyses might relate to a common metabolic abnormality in FCHL and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, recently, a major gene effect on insulin resistance in FCH has been suggested. 16 FCH is characterized by multiple lipoprotein phenotype expression; in 1 affected family, subjects may present with hyperTC, hyperTG or combined HLP. We demonstrate that insulin resistance is associated with lipid phenotype expression because FCH subjects based on hyperTG or combined HLP, were more insulin resistant compared with FCH subjects based on hyperTC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that FCH subjects are insulin resistant. [12][13][14][15][16][17][18] The aim of this study was to explore the role of insulin resistance in FCH lipid phenotype expression. Therefore, we studied in our large FCH cohort FCH subjects with different lipid phenotypes and the effect of changes in insulin resistance on intraindividual changes in lipid phenotype over a 5-year period.…”
mentioning
confidence: 99%
“…Segregation analyses have provided evidence for a major gene effect on apoB levels, 10-12 TG levels, 79 and the presence of sdLDL 7,11,15 and insulin resistance. 80 Genome-wide linkage studies have indicated that several chromosomal regions harbor genes that contribute to the lipid profile of FCH. In Finnish families with FCH, five loci on chromosomes 1q21, 2q31, 10p11.2, 10q11.2-10qter, and 21q21 were identified, whereas in Dutch families with FCH four loci on chromosomes 2p, 11p, 16q, and 19q were found.…”
Section: Genetics Of Fchmentioning
confidence: 99%